Combinatorial Chemistry: A Review - Singh, Hariraj; Sharma, Neha; Khinchi, M.P.; Gautam, Shubham; Kumawat, Ankit (Asian Journal of Pharmaceutical Research and Development, 2017)
Combinatorial chemistry represents a broad spectrum of techniques that are rapidly becoming a standard part of the medicinal chemist's tool kit. Combinatorial chemistry as a technique for the rapid synthesis of drug like compounds will continue to make a major impact on the way drug molecules are discovered. The development of combinatorial chemistry is timely and undoubtedly will contribute to the discovery of new drugs that can benefit mankind. This technique has definitely decreased the cost involved in new drug research and increased the chances of finding new lead molecules. Combinatorial chemistry reduces the time and cost associated with producing effective and competitive new drugs. Combinatorial chemistry comprises chemical synthetic methods that make it possible to prepare a large number (tens to thousands or even millions) of compounds in a single process. These compound libraries can be made as mixtures, sets of individual compounds or chemical structures generated by computer software. Combinatorial chemistry can be used for the synthesis of small molecules and for peptides.